Bollywood horrors : religion, violence and cinematic fears in India - Goldberg, Ellen; Sen, Aditi; Collins, Brian (London [England] : bBloomsbury, 2020)
"Bollywood Horrors is a wide-ranging collection that examines the religious aspects of horror imagery, representations of real-life horror in the movies, and the ways in which Hindi films have projected cinematic fears onto the screen. Part one, 'Material Cultures and Prehistories of Horror in South Asia' looks at horror movie posters and song booklets and the surprising role of religion in the importation of Gothic tropes into Indian films, told through the little-known story of Sir Devendra Prasad Varma. Part two, 'Cinematic Horror, Iconography and Aesthetics' examines the stereotype of the tantric magician found in Indian literature beginning in the medieval period, cinematic representations of the myth of the fearsome goddess Durga's slaying of the Buffalo Demon, and the influence of epic mythology and Hollywood thrillers on the 2002 film Raaz . The final part, 'Cultural Horror,' analyzes elements of horror in Indian cinema's depiction of human trafficking, shifting gender roles, the rape-revenge cycle, and communal violence."--
Preface, Brian Collins (Ohio University, USA) -- Introduction, Ellen Goldberg (Queen's University, Canada) , Aditi Sen (Queen's University, Canada) , and Brian Collins (Ohio University, USA) -- Part I: Material Cultures and Prehistories of Horror in South Asia -- 1. Monsters, Masala, and Materiality: Close Encounters with Hindi Horror Movie Ephemera, Brian Collins (Ohio University, USA) -- 2. Vampire Man Varma: The Untold Story of the "Hindu Mystic" Who Decolonized Dracula, Brian Collins (Ohio University, USA) -- Part II: Religion -- 3. Divine Horror and the Avenging Goddess in Bollywood, Kathleen Erndl (Florida State University, USA) -- 4. Horrifying and Sinister Tantriks, Hugh B. Urban (Ohio State University, USA) -- 5. Do you want to know the Raaz Tropes of Madness and Immorality in Bollywood Horror, Aditi Sen (Queen's University, Canada) -- Part III: Cinematic Fears -- 6. Cutural Horror In Dev : Man is the Cruelest Animal, Ellen Goldberg (Queens University, Canada) -- 7. Bandit Queen , Rape-Revenge, and Cultural Horror, Morgan Oddie (Queen's University, Canada) -- 8. Mardaani and the Trafficking of Women in India, Beth Watkins ( Allegheny College, USA) -- Epilogue: Is the Medium the Message? Rachel Dwyer (SOAS, University of London, UK) -- Bibliography -- Index
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Horror films -- India -- Mumbai -- History and criticism; Film: styles & genres; Electronic books